2014
DOI: 10.1080/14786419.2014.895724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing area on tocopherols, carotenoids and fatty acid composition ofPistacia lentiscusedible oil

Abstract: In this investigation, we aim to study, for the first time, the effect of the growing area on tocopherols, carotenoids and fatty acid content of Pistacia lentiscus fixed oil. Fruits were harvested from eight different sites located in the north and the centre of Tunisia. Tocopherols, carotenoids and fatty acid content of the fixed oils were determined. The highest carotenoid content was exhibited by Feija oil (10.57 mg/kg of oil). Oueslatia and Tabarka oils displayed the highest α-tocopherol content (96.79 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In fact, it has been determined that the fruit oil extracted from P. lentiscus growing in different regions of Tunisia is rich in antioxidants agents namely tocopherol (α-tocopherol and δ-tocopherol) and carotenoid species (lutein, zeaxanthin and β-carotene) (Mezni et al. 2014 ). The quantification of total tocopherol in PLFO has shown that α-tocopherol is the major tocopherol fraction (Mezni et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, it has been determined that the fruit oil extracted from P. lentiscus growing in different regions of Tunisia is rich in antioxidants agents namely tocopherol (α-tocopherol and δ-tocopherol) and carotenoid species (lutein, zeaxanthin and β-carotene) (Mezni et al. 2014 ). The quantification of total tocopherol in PLFO has shown that α-tocopherol is the major tocopherol fraction (Mezni et al.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of total tocopherol in PLFO has shown that α-tocopherol is the major tocopherol fraction (Mezni et al. 2014 ). Several previous studies demonstrated that α-tocopherol oral supplementation promotes the healing of chronic wounds (Gray 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidants described in the present study can explain the lower values of the autooxidation parameters. In fact, several researches reported that many vegetable oils were an important natural source of carotenoids such as Pistacia lentiscus that presented a value ranging between 5.8 and 10.57 mg/kg oil [27], but our studied oils have substantially higher amounts especially in fenugreek and sesame oils 56.78 mg/kg and 15.24 mg/kg, respectively. Carotenoids are the most important source of vitamin A.…”
Section: Discussionmentioning
confidence: 75%